Antimicrobial Resistance, Biocide Tolerance, and Bacterial Diversity of a Dressing Made from Coriander and Parsley after Application of Treatments Using High Hydrostatic Pressure Alone or in Combination with Moderate Heat - Javier Rodríguez López; Maria José Grande Burgos; Rubén Pérez Pulido; Belén Iglesias Valenzuela; Antonio Gálvez; Rosario Lucas (Foods, 2022)
The effects of high-hydrostatic pressure (HP) treatments (450 and 600 megapascals, MPa, for 5 min at temperatures of 22 °C and 50 °C) on the microbiota of a coriander and parsley dressing was studied via culture-dependent and culture-independent approaches. Samples were refrigerated for 20 days, with periodic counts of the culture media supplemented with, or without, antimicrobials. HP-treated samples showed significantly lower viable cell counts compared to untreated controls. Only the control samples yielded bacterial growth on media with antimicrobials (imipenem, cefotaxime, benzalkonium chloride), including mostly Pseudomonas and Lactobacillus. Bacillus and Paenibacillus were identified from pressurized samples. Few isolates showed higher tolerance to some of the biocides tested. Pseudomonads showed outstanding resistance to meropenem and ceftazidime. According to high-throughput sequencing analysis, the microbiota of the dressing control samples changes during storage, with a reduction in the relative abundance of Proteobacteria and an increase in Firmicutes. The composition of the residual microbiota detected during storage was highly dependent on the pressure applied, and not on the treatment temperature.